PENGEMBANGAN MEDIA PEMBELAJARAN VIDEO MODEL POE (PREDICT OBSERVE EXPLAIN) UNTUK MENULIS NARASI SISWA KELAS III SD - Eltri Roren Noprenka; Dessy Wardiah; Aldora Pratama (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
ABSTRACT The purpose of this study was to produce a POE (Predict Observe Explain) video product model for writing narratives for grade III students of SD Negeri 2 Sirah Pulau Padang that was valid and practical. This researcher used the ADDIE model which went through 5 stages (Analysis, Design, Development, Implementation, and Evaluation). The results of the validity analysis that the researcher obtained in the validation activity of the POE (predict observe explain) video learning media model, which were obtained from the three experts, namely media experts, material experts, and language experts, the researcher got a percentage value of 90.5%, including the valid criteria. While the practicality of the media based on the results of the student response questionnaire from the one-to-one individual test, small group media test, and field test got an average value of 97.3%, including the very practical criteria. Thus, it can be concluded that the development of the POE (Predict observe explain) video learning media model is declared valid and practical and can be used in subsequent learning activities.